Wayang Gedek [ (Dept. of Museums and Antiquities, 2002)
Documentary on wayang gedek, traditional Malay shadow plays which now can only be found in Northern Kedah. It has its roots from Thai nang talung. Instead of performing the Ramayana and Mahabharata epics, it tells popular local and Thai folk stories. Special characteristics are represented by the clowns such as Ai Thong and Keaw